2004
DOI: 10.1136/adc.2004.049247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage on breast milk antioxidant activity

Abstract: Background: Human milk, which contains compounds beneficial to infants, is often expressed and stored before use. Changes in its antioxidant activity with storage have not been studied. Objectives: To measure antioxidant activity of fresh, refrigerated (4˚C), and frozen human milk (220˚C), stored for two to seven days; to compare the antioxidant activity of milk from mothers delivering prematurely and at term; to compare the antioxidant activity of infant formulas and human milk. Methods: Sixteen breast milk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
88
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 37 publications
(23 reference statements)
4
88
1
4
Order By: Relevance
“…These advantages are even more important in preterm newborns, because they have an immature antioxidant defense system, since it develops during the course of gestation [5]. In addition, they are often exposed to oxidative stress caused by infections, mechanical ventilation, intravenous nutrition and blood transfusions [6]. Several studies have shown that the antioxidant capacity of HM is superior to infant formulas and bovine milk [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…These advantages are even more important in preterm newborns, because they have an immature antioxidant defense system, since it develops during the course of gestation [5]. In addition, they are often exposed to oxidative stress caused by infections, mechanical ventilation, intravenous nutrition and blood transfusions [6]. Several studies have shown that the antioxidant capacity of HM is superior to infant formulas and bovine milk [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Sari et al [4], the freezing samples of colostrum, transition and mature milk at -80 °C for two months did not preserve the antioxidant capacity. According to Hanna et al [6], the antioxidant capacity of HM also decreased with the storage time and refrigeration was better than freezing to preserve it, because the freezing for 48 hours caused greater losses than the refrigeration for seven days.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations